Janus kinase inhibitors in immunoinflammatory diseases: 10 years of clinical practice in rheumatology - E. L. Nasonov; T. V. Korotaeva (Научно-практическая ревматология, 2022)
Despite great advances in the diagnosis and treatment of Immune-mediated inflammatory diseases (IMIDs), which have led to a significant improvement in the prognosis in many patients, the central medical problems of this pathology – restoring the quality of life and reducing mortality to the population level – are far from being resolved. This served as a powerful stimulus for the study of new approaches to the pharmacotherapy of IMIDs, one of which is associated with the discovery of targets for small-molecule therapeutics that inhibit intracellular “signaling” molecules JAKs (Janus kinases). The current achievements, trends and recommendations regarding the use of JAK inhibitors in the treatment of IMIDs and also in the hyper-response phase of COVID-19 are reviewed.